The E-Strategy for Lean-Sigma Solutions, Latin American Case Study in a New Product Validation Process - Alba-Baena, Noé (Springer, Cham, 2018)
The international competition has challenged managers in Latin America to implement state-of-the-art methodologies for problem-solving and continuous improvement, and specifically, the production process validation has become an issue when it has to be completed in a short time span. Typically, the validation activities for critical equipment are performed at least a week prior to the official production launch. If, for any reason, the equipment gets into the plant late, any time taken by the validation process may impact the startup of the line. On the other hand, if production is started without validating the equipment, and performance is not as expected, then, the plant must start a cycle of process improvement activities to get the performance to the expected levels. In general, the continuous improvement activities are organized around two major methodologies: Lean Manufacturing and Six Sigma. While the Lean approach tends to be of a quick-fix type, it gets shorthanded when the causes are not so obvious, and deeper statistical analyses are required. On the other hand, Six Sigma works better when there is plenty of time to conduct all types of tests and analyses to achieve a good cost-effective solution. This chapter explores a combination of the Lean Manufacturing speed with the Six Sigma power of analysis, arranged as a set of sequential steps, for solving industrial problems and giving cost-effective solutions in a short time span. This is achieved by following a strategy identified by these authors as the E-Strategy, which is divided into two phases, the diagnostic and the solution phase. It uses a hierarchical approach of analysis for identifying the root cause of the problem. From the most frequent causes, the problems are eliminated adapting and using the most efficient set of tools. In the E-Strategy, as the complexity of the problem increases, the tools used get more specialized and elaborated. In this chapter, a case study is included as an example of the use of this methodology. The case study shows that the use of the Lean-Sigma approach is effective when following the E-Strategy sequence, and leads to improvements in overall performance. The description focuses on the efforts for increasing the conforming outcomes from a crimping process. A pull test is used for performance evaluation of the outcomes. Initial data shows an overall performance of a sigma level of 1.1. However, after following the E-Strategy, running a Taguchi experiment, and performing a series of adjustments a final process evaluation shows an increment to a sigma level of 5.5 for the performance, and a three times reduction in the variation of the process, achieving this solution in a short period of time of 3 days.